A high performance open-source syringe extruder optimized for extrusion and retraction during FRESH 3D bioprinting. (April 2021) - Tashman, Joshua W.; Shiwarski, Daniel J.; Feinberg, Adam W.
Graphical abstract: Abstract: Recent advances in embedded 3D bioprinting have significantly improved the resolution of individual filaments to below 100 µm; however, printing with such small filaments requires accurate extrusion of nanoliter volumes of bioink. Commercially available bioprinters and extruders are expensive and most utilize pneumatic control, which limits the minimum extrusion volume and prevents retraction (pulling bioink back into the reservoir), which is essential to printing high resolution features and complex internal geometry. Here we present a new generation of our open-source syringe pump designed for extrusion-based 3D bioprinting of soft materials: the Replistruder 4. The Replistruder 4 takes advantage of the geometry customizability and ease of 3D plastic printing while improving performance by integrating mass produced high-precision linear motion components. Simultaneously this new syringe pump remains compact and lightweight enough for several to be utilized on a 3D bioprinter for multimaterial bioprinting. To facilitate multiple use cases the Replistruder 4 is compatible with a range of syringes including disposable BD and Hamilton gastight syringes. In addition, we describe the process of designing clamps for other syringes. We demonstrate the performance of a Replistruder 4 with a 2.5 mL Hamilton gastight syringe by printing collagen type I constructs with individual filaments comprising 3.35 nL and patent channels down to 300 µm in width. With smaller volume Hamilton gastight syringes this performance can be further improved. Thus, the Replistruder 4 provides an open-source solution to print soft materials at the resolution limits of current embedded bioprinting platforms.